Steps to Marketing Timber - Chris Demers; Alan Long (EDIS)
Revised! SS-FOR-17, a 7-page fact sheet by Chris Demers and Alan Long, provides forest landowners some important guidelines to follow when planning and conducting a timber sale. Includes references. Published by the UF School of Forest Resources and Conservation, February 2010.